Prevalence and factors associated with urinary incontinence in institutionalized elderly the municipality of Santarém-PA (Research, Society and Development, 2022)
AbstractObjective: The objective of this research is to determine the prevalence and factors associated with urinary incontinence in institutionalized elderly and to explain the importance of physical therapy in the treatment of this dysfunction. Methods: This is a field research, where a scale was applied for the selection of research participants and then two questionnaires were Applied for data collection. Result and discussion: It was observed with the study that urinary incontinence represents a risk to the health of the elderly, as the data showed that the highest percentages were for items that indicate a significant loss of urine, which can end up leading this elderly person to a  functional deficit. Conclusion: It is concluded that urinary incontinence is associated with factors that are prevalent in the lives of institutionalized elderly people and that physiotherapy can act in a beneficial way not Only in the treatment, but also in the prevention of this dysfunction, providing this elderly with a better quality of life.